BENEFITS OF MASSAGE RELAXING IN SLEEP QUALITY (Fiep Bulletin - online, 2016)
Currently there are few studies in the field regarding the quality of sleep of individuals and massage, much of the population possess a sleep disorder are bruxism, insomnia, stress and many others that plague the restful sleep. This study aims to investigate the relationship between sleep and massage on the effects on sleep quality, we know that massage can promote deep relaxation of body structures such as muscles, arteries, tendons, so we can get to sleep deep REN6 also need a deep relaxation and added to a state of tranquility. Through this study, we understand that the relaxing massage is able to provide muscle and mental relaxation, causing a state conducive to sleep. The massage stimulates endorphin and serotonin which are the hormones responsible for feelings of pleasure, relaxation and also responsible for the deep sleep which we call REM sleep. The massage decreases cortisol one responsible for insomnia / stress, so a person receiving the massage will have less cortisol in the bloodstream that will result in an improvement in their quality of sleep. The literature with regard to the area of ??sleep related to massage is still very scarce, and therefore, we suggest more scientific study in the area to prove the amount of sessions, frequency of massages achievements and other systemic benefits it may result in body. We indicated practical research to raise more data on these benefits cited for this search.
Keywords: Massage; Relaxation; Sleep